2018
DOI: 10.1371/journal.pone.0191788
|View full text |Cite
|
Sign up to set email alerts
|

Microbubbles combined with ultrasound therapy in ischemic stroke: A systematic review of in-vivo preclinical studies

Abstract: BackgroundMicrobubbles (MBs) combined with ultrasound sonothrombolysis (STL) appears to be an alternative therapeutic strategy for acute ischemic stroke (IS), but clinical results remain controversial.ObjectiveThe aim of this systematic review is to identify the parameters tested; to assess evidence on the safety and efficacy on preclinical data on STL; and to assess the validity and publication bias.MethodsPubmed® and Web of ScienceTM databases were systematically searched from January 1995 to April 2017 in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 62 publications
0
32
0
Order By: Relevance
“…Hence, the ultrasound-induced blast of microbubbles may speed up the dissolution of thrombus. Microbubbles combined with TCD/TCCS were also applied to some other clinical trials, which might be able to get better clinical outcomes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the ultrasound-induced blast of microbubbles may speed up the dissolution of thrombus. Microbubbles combined with TCD/TCCS were also applied to some other clinical trials, which might be able to get better clinical outcomes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Given the culmination of transcranial Doppler, microbubble mediated, and intravascular sonothrombolysis research to clinical trials, it is still necessary to improve these technologies to address the observed clinical outcomes and limitations. There have been several extensive reviews on the benefits of thrombolytic mediated sonothrombolysis, microbubble mediated sonothrombolysis, and intravascular sonothrombolysis [60,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]. However, there still exists a clinical need for thrombolysis techniques which can decrease the risk of hemhorrage, vessel damage, and pulmonary embolism while also reducing the dose of thrombolytic agents and treatment times for patients.…”
Section: Purposementioning
confidence: 99%
“…The use of standard lipid shelled microbubbles such as Sonovue and Definity either alone or in combination with thrombolytic agents such as tPA have been studied and reviewed in great detail [67,75]. Microbubbles both alone and when used in combination with a thrombolytic agent for sonothrombolysis treatment uniformly outperform traditional thrombolytic treatments.…”
Section: Novel Contrast Agents For Sonothrombolysismentioning
confidence: 99%
“…Thrombolysis combined with ultrasound refers to the use of ultrasonic pulse to fracture emboli during thrombolysis. It increases the contact area of emboli and drug, promotes the dissolution of thrombus and makes good blood vessel dredging, which has become a hot spot of current research [32,33].…”
Section: Current Progress In Thrombolysis and Bridging Therapymentioning
confidence: 99%